Burócratas y legisladores. El control parlamentario sobre la administración pública (con atención en el caso peruano) - Patriau Hildebrandt, Cesar Enrique (2014)
This article discusses Parliamentary control over bureaucracies. In the first place, it reviews a number of studies that explain how the American Parliament influences public administration with the intention of guarantying that their intererst and preferences are protected in the decision making process. The American example demonstrates that the model of separation of powers does not take into account that Parliaments should avoid attempts to control the bureaucracy. In the second place, it analyses the Peruvian case and proposes a series of informal mechanisms by which the Parliament exerts influence over the bureaucracy and the public policy cycle.